SPONTANEOUS CEREBELLAR HEMATOMA: REVIEW OF 20 CASES (Iraqi Journal of Medical Sciences, 2016)
Background: Haemorrhages into structure of the posterior fossa pose unique risks due to limited space in this compartment and risk of hydrocephalus from compression of fourth ventricle. Most are neurosurgical emergencies requiring close monitoring and/or immediate evacuation.Objectives:To analyze therapy results obtained for surgically and conservatively treated patients. As well as to find prognostic parameters that can predict patient’s outcome.Method:Retrospective study conducted at the Neurosurgical Hospital in Baghdad, and Al-Shaheed Ghazi Al-Hariri for Surgical Specialties Hospital. All the information were collected from hospital records between December 2000 and December 2002 for 20 patients with spontaneous cerebellar hematoma and included Clinical data like the onset of symptoms and signs, durations, progression of clinical condition, past medical history. Records of vital signs and neurological signs. Records of laboratory studies include complete blood picture, blood grouping, blood biochemistry, prothrombin time, partial thromboplastin time, bleeding and clotting time). Records of CT-scan analyzed according to the site, size, and presence of associated pathology. Size of the hematoma estimated by the maximum axial diameter.Results:Age of patients in this study ranged from 6-76 Years .There was 12(60%) male and 8(40%) female patients with male to female ratio 1.5:1. Mortality in the conservatively treated group is 33%, while it is 54% in the surgically treated group. Hydrocephalus was present in 100% of patients in the surgical group, while it is not present in the conservatively treated patients.Conclusions:The most important prognostic factors were GCS score on admission, interval between hemorrhage onset and treatment, size and site of hematoma, presence of hydrocephalus, and fourth ventricular extension. Suboccipital craniectomy to evacuate the hematoma is the most effective procedure where surgical treatment is indicated.Keywords:Cerebellar hematoma, suboccipital craniectomy, ventriculostomy.
Keywords: Cerebellar hematoma; suboccipital craniectomy; ventriculostomy